Study of Leadership Style of Heads of regional Apparatus in Building Organizational Performance Programs Sustainable Environment Based - Taufik Hendayana; Agung Purwanto; Setia Budi (Universitas Muhammadiyah Enrekang, 2023)
In helping to carry out concurrent affairs and regional government affairs, the Regency/City Regional Head is assisted by regional officials. Juridically, the existence of district/city regional apparatus in Law Number 23 of 2014 consists of (1) Regional Secretariat, (2) DPRD Secretariat, (3) Inspectorate, (4) Regional Regional Services, (5) Regional Agency, And (6) District. Regarding regional apparatus, this is also strengthened by Government Regulation (PP) Number 18 of 2016 concerning Regional Apparatus. From these regional apparatus organizations, a head leads the organization. The leadership of heads of regional apparatus organizations is the main factor in achieving a better regional government system. Leaders determine how an organization, namely regional government, is run. The leadership style of heads of regional apparatus provides high levels of support and interacts more with subordinates/staff members of the organization, consults more, provides guidance motivation, and provides advice to achieve the goals of running the organization's performance program. Based on a sustainable environment. We also remain committed to/refer to and are guided by the RPJMD, Strategic Plan, Regional Regulations, APBD, and APBN. We do not violate the law in creating organizational performance programs based on a sustainable environment. Apart from that, the proposed leadership model/style is more ideal and rational by the hopes and desires of stakeholders, so the collaborative leadership style model is the one that best suits the situation and conditions of heads of regional apparatus in DKI Jakarta, namely collaborative, participatory leadership style, consultative leadership style, and transformational leadership style.